Percepções de fisioterapeutas sobre a relação da ciência com a prática clínica e uso de redes sociais como ferramenta de apoio à reabilitação baseada em evidências - Fernandes, Myllena Marcela Ganzert (2025)
Introduction: Evidence-based practice (EBP) integrates scientific knowledge, clinical experience, and patient preferences, making it ideal for healthcare. However, its application in physical therapy still faces challenges, such as the diversity of fields and the dynamics of care, which hinder access to and systematic incorporation of evidence. In this context, social media emerges as a tool for professional development, although it also raises questions about the reliability of the content. Objective: To understand physical therapists' perceptions of the incorporation of scientific knowledge into clinical practice and the use of social media to support evidence-based rehabilitation. Method: A qualitative, exploratory study was conducted with 28 physical therapists working in public and private clinics in different regions of Brazil, using semi-structured interviews. Results: The analysis identified two main themes: (1) applications of scientific knowledge in clinical practice, highlighting the central role of science in improving care and the use of strategies such as courses, mentoring, and peer exchanges; and (2) social media as an information tool, with Instagram and YouTube being the most cited, valued for their accessibility and encouragement of learning, but also associated with the risk of misinformation. Conclusion: Social media was perceived as a complementary resource to EBP, provided it is used critically. The effective incorporation of science into clinical practice requires overcoming technical and structural barriers.